2016
DOI: 10.1139/cjp-2016-0575
|View full text |Cite
|
Sign up to set email alerts
|

Bianchi type I and V solutions in f(R, T) gravity with time-dependent deceleration parameter

Abstract: In this paper, our attention is to reconstruct an appropriate model for Bianchi type I and Bianchi V space–times in f(R, T) gravity with the help of special law of deceleration parameter in connection to f(R, T) gravity (where R is the Ricci scalar and T is the trace of energy–momentum tensor). We solve the modified Einstein field equations for anisotropic and homogeneous Bianchi type V space–time. The solution of field equations facilitates finding out the physical as well as kinematical quantities. We explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The kinematical behaviour of LVDP along with null energy condition (NEC) has been explored in the framework of f (R, T ) gravity for Bianchi type -I and V space-time. 58 Akarsu et al 59 have described the fate of the universe through parametrization q = q 0 + q 1 (1 − t t0 ), which is linear in cosmic time t, along with two well-known additional parametrization of the DP q = q 0 + q 1 z and q = q 0 + q 1 (1 − a a0 ), where z and a are the redshift parameter and scale factor respectively. Furthermore, they have studied the dynamics of the universe in comparison with the standard ΛCDM model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinematical behaviour of LVDP along with null energy condition (NEC) has been explored in the framework of f (R, T ) gravity for Bianchi type -I and V space-time. 58 Akarsu et al 59 have described the fate of the universe through parametrization q = q 0 + q 1 (1 − t t0 ), which is linear in cosmic time t, along with two well-known additional parametrization of the DP q = q 0 + q 1 z and q = q 0 + q 1 (1 − a a0 ), where z and a are the redshift parameter and scale factor respectively. Furthermore, they have studied the dynamics of the universe in comparison with the standard ΛCDM model.…”
Section: Introductionmentioning
confidence: 99%
“…The kinematical behaviour of LVDP along with null energy condition (NEC) has been explored in the framework of f (R, T ) gravity for Bianchi type -I and V space-time. 58 Akarsu et al 59 have described the fate of the Magnetized strange quark model with Big Rip singularity in f (R, T ) gravity 5…”
mentioning
confidence: 99%
“…Using metric formalism, they derived the associated field equations for some specific cases. In [28][29][30][31][32], some interesting cosmological f (R, T ) models have been developed by employing various scenarios namely, auxiliary scalar field, dark energy models and anisotropic universe models. In literature [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], different cosmological applications of f (R, T ) gravity have been discussed like energy conditions, thermodynamics, exact and numerical solutions of field equations with different matter content, phase space perturbation, compact stars and stability of collapsing objects etc.…”
Section: Introductionmentioning
confidence: 99%
“…A string solution in the LRS case was solved by Kanakavalli and Rao [25] by taking the equation of state for strings. Zubair et al [26] found Bianchi types I and V solutions by using a linear deceleration parameter and taking the expansion proportional to the expansion.…”
Section: Introductionmentioning
confidence: 99%